PENERAPAN STANDAR INTERVENSI KEPERAWATAN INDONESIA DENGAN PROMOSI HARGA DIRI PADA PASIEN SKIZOFRENIA DI RSJ Prof. Dr. SOEROJO MAGELANG - Erika Aprilliya; Erna Erawati; Suyanta Suyanta; Suharsono Suharsono (NHM PRESS, 2023)
Schizophrenia is a medical diagnosis that has mental problems in individuals with abnormal social behavior. Schizophrenia has negative symptoms, one of which is low self-esteem. Low self-esteem is a negative view that is owned by himself so that his self-confidence and self-esteem are lost. The aim of the research is to describe the application of Indonesian nursing intervention standards with the promotion of self-esteem, namely motivation to accept challenges or new things. Motivation to accept challenges/new things aims to restore self-confidence and explore one's abilities. This research uses a descriptive method in the form of a case study. The results of this study indicate that there is an increase in low self-esteem in patients.